Action for Children: a model for stimulating local fundraising in low- and middle-income countries. Issue 5 (3rd July 2016) - Wiggers, Robert
ABSTRACT: This practical note reflects on the conclusions and learning from an evaluation of the Action for Children programme in four countries: Brazil, India, Kenya, and South Africa. Action for Children was developed by Wilde Ganzen to enhance diversity in funding and organisational sustainability through increased local resource mobilisation and, more specifically, local fundraising. The note looks at the challenges the programme sought to address, and examines the findings from the evaluation, plus the long-term prospects of sustainability for the local partners.